Challenges To Investigator Professionality In Law Enforcement: A Rule Of Law And Good Governance Perspective - Widijowati, Rr. Dijan; Restu Adhie Charisma, Restu Adhie Charisma (KRTHA BHAYANGKARA, 2025)
Enforcement the law in Indonesia does not can released from function and existence investigator as part from structure law. Investigators who have function enforcement law in fact not yet capable realize ideals law community. Complaints to The Chief of Police and the National Human Rights Commission to culminating in implementation title case specifically at the Criminal Investigation Unit of the Indonesian National Police Headquarters is one of the proof concrete investigator Not yet capable carry out task in accordance with need law community. The research method used is method juridical normative with approach studies case. Data collected through studies more literature carry on done analysis For can answer problem function and existence investigator in community. Research results show various obstacle professionalism investigator in carry out enforcement law. Implementation rule of law and good governance in function and existence investigator considered as step strategic for build integrity investigator in carry out function enforcement law. Strengthening regulation, supervision and cultural reform is step urgent to ensure fair and certain investigation law.